How does China's digital government construction affect enterprise exploratory innovation? Insights based on invention knowledge inertia - ZhaoShuai Ren; QiaoYi Gao; Tong Sun; Min Sun (Digital Business)
Today, digital governments are creating novel digital business environments to promote enterprise innovation. How can enterprises benefit from this while minimizing the risks of working with the digital government?We explored this issue using data from China's1528 A-share firms over a decade. We find that China's digital government construction (DGC) significantly promotes firms' exploratory innovation (EI). Moreover, the enterprise's invention knowledge inertia (IKI) is an important mediation to develop its exploratory innovation in response to the construction of digital government. However, during this process, whether enterprises can maintain low risk and continuously promote EI by leveraging IKI is moderated by the extent of knowledge openness within the senior leadership team (KOM). For instance, the diversified knowledge of executives with financial backgrounds weakens the DGC→IKI, and the effect is obvious in state-owned and high-tech enterprises. In contrast, knowledge without such backgrounds strengthens the IKI→EI.This study provides valuable insights into government-enterprise cooperation, emphasizing the role of innovation knowledge inertia and clarifying the debate on whether knowledge inertia has a positive or negative impact on innovation.